Prophylactic Use of Ganoderma lucidum Extract May Inhibit Mycobacterium tuberculosis Replication in a New Mouse Model of Spontaneous Latent Tuberculosis Infection - Zhan, Lingjun; Tang, Jun; Lin, Shuzhu; Xu, Yanfeng; Xu, Yuhuan; Qin, Chuan (Frontiers in Microbiology, 2016)
A mouse model of spontaneous latent tuberculosis infection (LTBI) that mimics LTBI in humans is valuable for drug/vaccine development and the study of tuberculosis. However, most LTBI mouse models require interventions, and a spontaneous LTBI mouse model with a low bacterial load is difficult to establish. In this study, mice were IV-inoculated with 100 CFU Mycobacterium tuberculosis H37Rv, and a persistent LTBI was established with low bacterial loads (0.5 1.5log10 CFU in the lung; < 4log10 CFU in the spleen). Histopathological changes in the lung and spleen were mild during the first 20 weeks post-inoculation. The model was used to demonstrate the comparative effects of prophylactic and therapeutic administration of Ganoderma lucidum extract (spores and spores lipid) in preventing H37Rv replication in both lung and spleen. H37Rv was inhibited with prophylactic use of G. lucidum extract relative to that of the untreated control and therapy groups, and observed in the spleen and lung as early as post-inoculation week 3 and week 5 respectively. H37Rv infection in the therapy group was comparable to that of the untreated control mice. No significant mitigation of pathological changes was observed in either the prophylactic or therapeutic group. Our results suggest that this new LTBI mouse model is an efficient tool of testing anti-tuberculosis drug, the use of G. lucidum extract prior to M. tuberculosis infection may protect the host against bacterial replication to some extent.